Culturally responsive conversations connecting with your diverse school community - Lee, Marina Minhwa; Leighton, Seth (Jossey-Bass, a Wiley brand, 2023)
"This book cultivates the capacity of educators to respond to the changes that come along with the increasing number of culturally diverse students in American classrooms. The way educators respond and pivot their pedagogies to be inclusive of all cultures will determine the future of not only American schools, but American society. This book provides educators and families with a connection to educational outcomes with a deeper understanding of the diversity of approaches to education within different cultural perspectives and how to successfully navigate the relationships and activities that make up the landscape of US schools. Each subject area will cover expectations in US culture, Immigrant realities, and suggestions and practical exercises to address these realities in the classroom."--Provided by publisher.